INFLUENCE OF KNOWLEDGE ENTREPRENEURSHIP, CREATIVITY AND THE ENVIRONMENT FAMILY TO INTEREST ENTREPRENEUR STUDENT OF SMK NEGERI 2 SUKABUMI - Suryani, Cania; Purwana, Dedi; Fidhyallah, Nadya Fadillah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
The purpose of this study was to determine the effect of entrepreneurial knowledge, creativity, and family environment on the entrepreneurial interests of SMK Negeri 2 Sukabumi students. This research is a causal associative research with a quantitative approach and uses a survey method. The population in this study were students of SMK Negeri 2 Sukabumi. The sampling technique used purposive sampling technique with certain considerations so that the population in this study was 326 students and a sample of 77 students who had been calculated using the Slovin formula with 10% equality. The data analysis technique used in this study uses Structural Equation Modeling (SEM) which is calculated using SmartPLS software version 3.3.9. The results of this study indicate that entrepreneurship knowledge has a positive and significant effect on students’ interest in entrepreneurship, creativity has a positive and significant effect on students’ interest in entrepreneurship and the family environment has a positive and significant effect on students’ interest in entrepreneurship.